The Torngat Orogen in the North River-Nutak transect area of Nain and Churchill provinces - Ermanovics, Ingo; Van Kranendonk, Martin (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1990)
Summary The Archean Nain Province, part of the North Atlantic craton, collided obliquely with the eastern Churchill Province 1900-1800 million years ago. The eastern Churchill Province (Rae Province) and portions of the western Nain Province were deformed by sinistral transcurrent shear at syn- and post-peakgranulite- to amphibolite-facies conditions during the collislonal phase of the Torngatorogeny. Tectonic remnants of the Early Proterozoic Ramah Group were structurally inter-leaved with Nain Province rocks in the tectonic foreland during this orogeny. In the Churchill Province, the orogeny deformed felsic and mafic igneous rocks intruded into sediments deposited on a foredeep shelf of inferred metaplutonic rocks of the eastern Churchill Province. The effects of orogeny extend east of the tectonic foreland as waning metamorphic grade across 85 km of the Nain Province.